Theoretical Study of Ternary CoSP Semiconductor: A Candidate for Photovoltaic Applications. Issue 10 (20th August 2019) - Houari, Abdesalem; Benissad, Fares
Abstract: The electronic structure of pyrite‐type cobalt phosphosulfide (CoSP) is studied using density‐functional theory. The calculated band structure reveals the non‐magnetic semiconducting character of the compound. The electronic structure is described using the electronic band structure and the densities of states. A band gap of 1.14 eV is computed within standard GGA, a value which is enhanced using hybrid functional. It separates the upper part of the valence band dominated by Co‐ 3d‐t 2 g states from the lower part of the conduction band made exclusively of Co‐ 3d‐e g, above of which lie S‐ 3p and P‐ 3p ones. The obtained values are suitable for applications in solar cells, according to Shockley–Queisser theory of light‐to‐electric conversion efficiency. The origin of the larger CoSP band gap, with respect to the one of the promising FeS2 compound, is explained and the chemical bonding properties are addressed. A comparative picture is established where several similarities are found, suggesting that CoSP could be of great practical interest in photovoltaics. Abstract : The electronic structure of pyrite‐type cobalt phosphosulfide (CoSP) is studied using density‐functional theory. The obtained values are suitable for applications in solar cells, according to Shockley–Queisser theory of light‐to‐electric conversion efficiency. A comparative picture is established where several similarities are found, suggesting that CoSP could be of great practical interest in photovoltaics.